Financing for Development : Enhancing the Financial Safety Net for Developing Countries---Further Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
PRGT-eligible members make considerable use of Fund concessional financing. Since 2010, 56 percent of Fund arrangements have involved a PRGT-facility. This paper examines a number of issues raised by Executive Directors and the International Monetary and Financial Committee (IMFC) since the issuance to the Board of the June 2015 staff paper on enhancing the financial safety net for developing countries (IMF, 2015a). This paper concludes that there is a need to clarify guidance in some areas pertaining to PRGT policies. This will be done through an early revision of the LIC Handbook, which is already underway. The paper does not propose changes to the Fund's concessional facilities at this juncture. A comprehensive review of PRGT (Poverty Reduction and Growth Trust) resources and facilities is planned for 2018.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet